2016
DOI: 10.1097/hcr.0000000000000194
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Rehabilitation Utilization in Older Adults With Chronic Obstructive Pulmonary Disease, 2003 to 2012

Abstract: Utilization of PR during the study period increased only 1.1% in these Medicare beneficiaries with COPD and remained low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 38 publications
(34 reference statements)
2
43
0
1
Order By: Relevance
“…30,31 Major challenges in realising the effectiveness of pulmonary rehabilitation are that a proportion of people who have COPD and hence AECOPD have not been diagnosed, 32 and a large proportion of those who have been diagnosed and are eligible for pulmonary rehabilitation are not being referred 22 . In addition the England and Wales national COPD audit programme, which includes data from both the acute hospital settings and primary care, reported that 31% of patients referred for rehabilitation did not attend the initial assessment, and 40% of those referred did not complete the programme 22,33 .…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Major challenges in realising the effectiveness of pulmonary rehabilitation are that a proportion of people who have COPD and hence AECOPD have not been diagnosed, 32 and a large proportion of those who have been diagnosed and are eligible for pulmonary rehabilitation are not being referred 22 . In addition the England and Wales national COPD audit programme, which includes data from both the acute hospital settings and primary care, reported that 31% of patients referred for rehabilitation did not attend the initial assessment, and 40% of those referred did not complete the programme 22,33 .…”
Section: Discussionmentioning
confidence: 99%
“…The American Association of Cardiovascular and Pulmonary Rehabilitation website lists fewer than 600 certified programs in the US for the estimated 16 million Americans diagnosed with COPD. An analysis of more than 33 000 Medicare beneficiaries with COPD from 1 January 2003 to 31 December 2012 showed that only 1239 people (3.7%) used pulmonary rehabilitation in 2012, with a dismal 1.1% increase in use over the 10 years 90. There is geographic disparity in availability because most programs are located at tertiary care centers and require patients to travel to the program two or three times a week 293032.…”
Section: Chronic Obstructive Pulmonary Disease and Pulmonary Rehabilimentioning
confidence: 99%
“…Despite this, pulmonary rehabilitation is only available to a small sliver of COPD patients who could benefit [4,5], as compared to the almost universal availability of bronchodilator therapy. The reasons for this discrepancy are hard to understand, since both therapies receive strong international recommendation as standard of care [6] and some analyses judge pulmonary rehabilitation to have higher cost-effectiveness than bronchodilator therapy [7].…”
mentioning
confidence: 99%